Responses of seaweeds that use CO2 as their sole inorganic carbon source to ocean acidification: differential effects of fluctuating pH but little benefit of CO2 enrichment - Damon Britton; Craig Mundy; McGraw, CM; Revill, AT; Catriona Hurd (2019)
Laboratory studies that test the responses of coastal organisms to ocean acidification (OA) typically use constant pH regimes which do not reflect coastal systems, such as seaweed beds, where pH fluctuates on diel cycles. Seaweeds that use CO 2 as their sole inorganic carbon source (non-carbon dioxide concentrating mechanism species) are predicted to benefit from OA as concentrations of dissolved CO 2 increase, yet this prediction has rarely been tested, and no studies have tested the effect of pH fluctuations on non-CCM seaweeds. We conducted a laboratory experiment in which two ecologically dominant non-CCM red seaweeds ( Callophyllis lambertii and Plocamium dilatatum ) were exposed to four pH treatments: two static, pH T 8.0 and 7.7 and two fluctuating, pH T 8.0 ± 0.3 and 7.7 ± 0.3. Fluctuating pH reduced growth and net photosynthesis in C. lambertii , while P. dilatatum was unaffected. OA did not benefit P. dilatatum , while C. lambertii displayed elevated net photosynthetic rates. We provide evidence that carbon uptake strategy alone cannot be used as a predictor of seaweed responses to OA and highlight the importance of species-specific sensitivity to [H + ]. We also emphasize the importance of including realistic pH fluctuations in experimental studies on coastal organisms.